2012
DOI: 10.1002/bio.2365
|View full text |Cite
|
Sign up to set email alerts
|

Determination of carbamazepine in human urine and serum samples by high‐performance liquid chromatography with post‐column Ru(bipy)‐Ce(SO4)2 chemiluminescence detection

Abstract: A novel, sensitive and rapid CL method coupled with high-performance liquid chromatography separation for the determination of carbamazepine is described. The method was based on the fact that carbamazepine could significantly enhance the chemiluminescence of the reaction of cerium sulfate and tris(2,2-bipyridyl) ruthenium(II) in the presence of acid. The chromatographic separation was performed on a Kromasil® (Sigma-Aldrich) TM RP-C18 column (id: 150 mm × 4.6 mm, particle size: 5 µm, pore size: 100 Å) with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The validity of this less-invasive method was also more recently confirmed by another group of researchers, who demonstrated a good repeatability of saliva sampling [30]. Other studies have shown the possibility to measure carbamazepine levels in urine samples with good accuracy [31,32]. As for other drugs, the TDM of carbamazepine (and often the other required screening tests) is not performed enough, especially in mental-health settings [76,77], despite being a mandatory assessment.…”
Section: Tdm and Mood Stabilizersmentioning
confidence: 84%
“…The validity of this less-invasive method was also more recently confirmed by another group of researchers, who demonstrated a good repeatability of saliva sampling [30]. Other studies have shown the possibility to measure carbamazepine levels in urine samples with good accuracy [31,32]. As for other drugs, the TDM of carbamazepine (and often the other required screening tests) is not performed enough, especially in mental-health settings [76,77], despite being a mandatory assessment.…”
Section: Tdm and Mood Stabilizersmentioning
confidence: 84%